The Influence of Psychological Safety, Transformational Leadership on Employee Engagement of the Company through the Meaning of Work - Prihartati, Ika; Agung Priambodo, Ervin; Budiantoro, Anandha (Riviera Publishing, 2023)
The success of organizational goals can be achieved effectively when supported by employees who have a deep commitment to the organization. Strong Employee Engagement will drive motivation, enhance productivity, foster harmonious relationships, and provide significant benefits to both parties. This research aims to understand and analyze the influence of psychological safety and transformational leadership on employee engagement through work meaning. The research methodology used a quantitative descriptive approach. Data collection was done through a questionnaire that assessed employee behaviors in the workplace, their interpretations, and interactions as leaders or subordinates in the organizational context. This study was conducted at PT Bio Farma (Persero) in Bandung, involving 253 respondents. Path analysis was used to evaluate hypotheses based on data collected from a 46-statement questionnaire. The results of this research indicate that good Psychological Safety, effective Transformational Leadership, and the presence of meaning in work (Work Meaning) play crucial roles in enhancing Employee Engagement at PT Bio Farma. Specifically, Psychological Safety and Work Meaning have the most significant direct impact on the level of employee engagement, each accounting for 65% and 60%, respectively. The findings of this research have important implications for companies looking to enhance employee engagement by focusing on psychological safety and promoting a transformational leadership style that facilitates meaningful work for employees.